El rey ángel en tiempos de valido e imperio - Galdeano Carretero, Rodolfo (Hispania sacra, 2023)
Rodrigo de Herrera's work, Del cielo viene el buen rey, and Calderón de la Barca's apocryphal, El rey ángel, show the continuity and vitality of the ancient apologue known as "The Superb Emperor", which during the first Modern Age was also the basis for other dramatic texts in the main European languages. Based on the interpretation of certain biblical passages from The Book of Daniel that exemplify the sin of pride against God, the two pieces that concern us - halfway between comedy and self-confessional - mutated the original meaning of the story into the model of the angel king. This model revealed the contradictions between a confessional society and the bureaucratic practices of the monarchy and the king's exercise of absolute power.